Use of Autonomy-Supportive or Controlling Motivational Style of Teaching with Special Education and Rehabilitation Teachers - Černe, Tanja (Revija za elementarno izobraževanje, 2022)
Self-determination theory assumes that the motivational teaching style significantly influences the motivational orientation of students, as well as their memorization, automation of learning skills and educational achievements. The research included 30 special education and rehabilitation teachers, who provide additional professional assistance in primary school and who were asked to complete a self-evaluation questionnaire based on self-determination theory. The following facts were ascertained: the autonomy-supportive style of teaching prevails; the presence of one characteristic does not condition the presence of another characteristic; and the use of style does not depend on the years of experience.
Keywords: self-determination theory, autonomy-supportive teaching style, controlling teaching style, special education and rehabilitation teachers, students with specific learning difficulties